The Impact of Managerial Leadership Styles in Promoting the Intellectual Security of Employees - A descriptive study on King Abdulaziz University - - Al-Zahrani, Mona Ali Abdullah; Al-Qurashi, Suzan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to recognize the effect of patterns of administrative leadership embodied in the leadership patterns of ‘autocracy, democracy and liberalism’ on strengthening intellectual security among staff and personnel – of both genders – of King Abdul Aziz University in Jeddah. To this aim, the researcher has employed the descriptive analytical approach. A questionnaire was specifically designed to have 48 questions. Community of the study was composed of 4183 employees, of both genders, in King Abdul Aziz University. The study was conducted on a sample group composed of 359 administrative employees who were randomly selected. Data and information were statistically processed by using the SPSS program. Findings of the study revealed the following. A positive effect with statistical indication was revealed for both leadership patterns of democracy and liberalism on strengthening intellectual security from the viewpoint of administrative staff and personnel in King Abdul Aziz University. Nonetheless, findings pointed out absence of any effect with statistical indication of autocratic pattern of leadership on strengthening intellectual security among administrative staff and personnel in King Abdul Aziz University. Findings further revealed statistically indicated differences in the average viewpoints of administrative staff and personnel over Chancellors’ exercise of both patterns of autocratic and democratic leadership according to the variable of gender. There were no statistically indicated differences in the average viewpoints of administrative staff and personnel over the Chancellors’ exercise of liberal pattern of leadership according to the variable of gender. In addition, the first pattern of leadership and the most commonly practiced by University Chancellors from the viewpoint of staff and personnel was the democratic pattern of leadership, followed by liberal pattern and eventually the autocratic pattern of leadership. There were no statistically indicated differences in the average viewpoints of staff and personnel of both genders over Chancellors’ exercise of autocratic, democratic and liberal patterns of leadership according to the variables of ‘age, academic degree, rank, position and years of active service’. The study has made a number of recommendations as follows. Practice of the democratic pattern of leadership shall be strengthened by Top Management in all its aspects among managers and directors in King Abdul Aziz University. Corrective measures should be taken to practice the democratic and liberal patterns of leadership through holding training courses. The concept of intellectual security among staff and personnel at all administrative levels should be further established through holding seminars and workshops.